Hypertonic Dextrose Prolotherapy Injection Improves Clinical Outcomes in Shoulder Impingement Syndrome with Diabetes Mellitus: A Quasi-Experimental Study - Pane, Rita Vivera; Al Hajiri, Aufar Zimamuz Zaman ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2025)
Background: Shoulder impingement syndrome (SIS) is the most common cause of shoulder pain. Current conservative management approaches often require years for patients to achieve pain relief. This study aimed to identify the effects of hypertonic dextrose prolotherapy (HDP) injections on pain levels and shoulder functionality in SIS patients with diabetes mellitus. Methods: A quasi-experimental study was conducted recruiting SIS patients at Hajj Regional Hospital, Surabaya, Indonesia, from January 2022 to December 2023. The study group was divided into two: the HDP group, which received a 5 mL injection of HDP at a concentration of 20%, and the control group, which received pharmacotherapy and regular rehabilitation therapy. While the control group received regular pharmacotherapy and rehabilitation therapy only. The study outcomes assessed were the Numeric Rating Scale (NRS) and shoulder Active Range of Motion (AROM). The evaluation was conducted three times: before the intervention, immediately after the intervention, and two weeks after the intervention. Results: A total of 20 study participants were divided into two groups: 10 in the HDP group and 10 in the control group. Inter- and intragroup analyses showed significant differences in NRS mean values between the HDP and control groups (p < 0.05). Similarly, AROM analysis showed significant differences in mean values between the HDP and control groups, both inter- and intra-group (p < 0.05). Conclusions: HDP injection reduces pain intensity and improves shoulder AROM within two weeks after injection.